The cause of Cushing's disease. - Grossman, A (2000)
Cushing's disease is one of the most fascinating disorders in the whole of endocrinology, in which a minute tumour in the pituitary gives rise to a whole panoply of symptoms, signs and changes in mood and behaviour. Recent research has begun to identify the molecular changes in these tumours underlying the reduced sensitivity of the tumour cells to normal feedback regulation and cell cycle control, which may eventually lead to specific gene therapy.